KUŞAK HAKLARI BAĞLAMINDA İNSAN HAKLARI ÖLÇEĞİ - Durul, Ferzan; Er, Kemal; Solmaz, Umut (Fırat University, 2022)
İnsan hakları doğumdan itibaren her insanın sahip olduğu, hiçbir kurum ya da kişinin engel olamayacağı, bir başkasına devredilemeyecek, vazgeçilemeyecek hakları kapsamaktadır. Bu sebepten insanların, onurlu, sağlıklı ve mutlu yaşamaları için hayati öneme sahiptir. Ancak, insan hakları hayati öneme sahip olduğu halde, dünyadaki tüm ülkelerde insan hakları sorunları yaşanmaktadır. İnsan hakları sorunlarını tespit edebilmek için ise, ölçebilmek gerekmektedir. Buradaki çalışmada da, toplumdaki insan haklarıyla ilgili sorunları ölçebilmek amacıyla kuşak hakları bağlamında insan hakları ölçeği (KHÖ) geliştirilmiştir. Ölçeğin geliştirilmesi sırasında, literatür bilgisi doğrultusunda, kuşak haklarının birbirinden ayrılamayacağı ilkesinden hareket edilmiştir. Ölçekte “5”li likert ölçeğine göre hazırlanmış “40” soru bulunmaktadır. Ölçek örneklemi 764 katılımcının anketleri tamamlamasıyla oluşturulmuştur. Ölçeğin geçerlik ve güvenirlik çalışmaları için, IBM SPSS 25 programıyla Açımlayıcı Faktör Analizi (AFA), Lisrel 8.72 programıyla Doğrulayıcı Faktör Analizi (DFA) yapılmıştır. İç tutarlılık güvenirliliğini ölçmek için kullanılan Cronbach Alpha değeri 0,97 bulunmuştur. AFA sonucu ölçeğin “4” faktörlü olduğu bulunmuştur. AFA, DFA analizleri sonuçlarının da gösterdiği gibi, KHÖ, geçerli ve güvenilir bir ölçme aracıdır.

Human rights cover the rights that every person has from birth, that no institution or person can prevent, that cannot be transferred to another person, that cannot be waived. For this reason, it is of vital importance for people to live dignified, healthy and happy lives. However, although human rights are of vital importance, human rights problems are experienced in all countries of the world. In order to detect human rights problems, it is necessary to measure them. In this study, the human rights scale (KHÖ) was developed in the context of generational rights in order to measure the problems related to human rights in the society. During the development of the scale, in line with the literature, the principle that generational rights cannot be separated from each other was taken into consideration. There are “40” questions prepared according to the “5” Likert scale in the scale. The scale sample was created after 764 participants completed the questionnaires. For the validity and reliability studies of the scale, Exploratory Factor Analysis (EFA) with IBM SPSS 25 program and Confirmatory Factor Analysis (CFA) with Lisrel 8.72 program were performed The Cronbach Alpha value used to measure the internal consistency reliability was found to be 0.97. As a result of EFA, the scale was found to have “4” factors. As the results of the EFA and CFA analyzes show, the HRQ is a valid and reliable measurement tool.
Human Rights Scale In The Context Of Generation Rights